Pengaruh Pembelajaran CORE Melalui Pendekatan Open-Ended terhadap Kemampuan Berpikir Kritis Matematis Siswa - Ayu Naili Rohmah; Himmatul Ulya (Universitas PGRI Adi Buana Surabaya, 2021)
The lack of optimal mathematical critical thinking ability of students becomes a problem that will be discussed. This is due to the selection of learning models and approaches used in the teaching and learning process. Mathematical critical thinking is one of the skills needed to solve a problem. The purpose of this study is to determine the influence of CORE learning models (Connecting, Organizing, Reflecting, Extending) through the Open-Ended approach to students' mathematical critical thinking skills. By using core learning models (Connecting, Organizing, Reflecting, Extending) through an Open-Ended approach students can solve problems without being limited with one solution only. It can provide opportunities for students to develop and analyze their ideas to solve the maslaah given so as to improve students' mathematical critical thinking skills. This study is a literature study on efforts to improve students' mathematical critical thinking skills using CORE learning models (Connecting, Organizing, Reflecting, Extending) through an Open-Ended approach.